The challenge of healthcare for consensus public reason - Hordern, J (Philosophy Documentation Center, 2021)
This article argues that religious and other "non-public" reasoning can have a legitimate and beneficial role in justifying health-related resource allocation decisions affecting individuals, subpopulations and whole communities. Section I critically examines Norman Daniels’s exclusion of such reasoning from such justifications. Section II shows the inadequacy of Daniels’s approach to healthcare as a matter of basic justice, arguing that consensus public reason is indeterminate in certain areas of healthcare policy, including the use of life-sustaining resources and issues related to risk and responsibility. Section III shows how resource allocation decision-making can appropriately incorporate religious and "non-public" reasoning via the medical professional practice of collaborative deliberation.